Perempuan Kuasa: Citra Perempuan dalam Cerpen Laila Karya Putu Wijaya - Erika Citra Sari Hartanto (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2012)
There are many male authors who take woman as the theme in their literary works. It is unavoidably that the image of women in those literary works either positive or negative. One of literary works which took woman as the theme and written by male author is a short story titled Laila by Putu Wijaya. It is interesting to find out how the image of women is described by the author by using feminism literary critic. Apparently, the description of woman is positive. For him, woman should get respect from man and have strong personality.